Model-Based Optimization of Ripening Processes with Feedback Modules - Spinola, Michele; Keimer, Alexander; Segets, Doris; Leugering, Günter; Pflug, Lukas (Chemical Engineering & Technology, 2020)
In order to obtain high-quality particulate products with tailored properties, process conditions and their evolution in time must be chosen appropriately. Although the efficiency of these products depends on their dispersity in several dimensions, in established processes the particle size is usually the decisive variable to adjust. As part of the synthesis of these products, feedback modules are often incorporated so that a time-dependent ratio of the obtained product can flow back into the system. Moreover, the synthesis should be an energy- and resource-efficient process. To provide a means of ensuring this requirement, a model- and gradient-based, numerically efficient optimization tool for particle synthesis is presented which was developed to describe population balance equations incorporating feedback terms.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Feedback modules; Gradient-based optimization; Population balance equation; Ripening process